Wideband switchable dual-functional terahertz polarization converter based on vanadium dioxide-assisted metasurface. (January 2022) - Yan 严, De-Xian 德贤; Feng 封, Qin-Yin 覃银; Yuan 袁, Zi-Wei 紫微; Meng 孟, Miao 淼; Li 李, Xiang-Jun 向军; Qiu 裘, Guo-Hua 国华; Li 李, Ji-Ning 吉宁
Abstract : The terahertz technology has attracted considerable attention because of its potential applications in various fields. However, the research of functional devices, including polarization converters, remains a major demand for practical applications. In this work, a reflective dual-functional terahertz metadevice is presented, which combines two different polarization conversions through using a switchable metasurface. Different functions can be achieved because of the insulator-to-metal transition of vanadium dioxide (VO2 ). At room temperature, the metadevice can be regarded as a linear-to-linear polarization convertor containing a gold circular split-ring resonator (CSRR), first polyimide (PI) spacer, continuous VO2 film, second PI spacer, and gold substrate. The converter possesses a polarization conversion ratio higher than 0.9 and a bandwidth ratio of 81% in a range from 0.912 THz to 2.146 THz. When the temperature is above the insulator-to-metal transition temperature (approximately 68 °C) and VO2 becomes a metal, the metasurface transforms into a wideband linear-to-circular polarization converter composed of the gold CSRR, first PI layer, and continuous VO2 film. The ellipticity is close to −1, while the axis ratio is lower than 3 dB in a range of 1.07 THz–1.67 THz. The metadevice also achieves a large angle tolerance and large manufacturing tolerance.